Study on the influencing factors of ecological spatial grouping optimization in the huangshan region based on entropy weight topsis - Le Zhang; Qiqi Rao; Mingxia Yuan; Yanlong Guo (PLoS ONE, 2025)
This study evaluates and analyzes the influencing factors of ecological spatial configuration optimization in the Greater Huangshan Region. By identifying and assessing these factors, it aims to reveal the mechanisms underlying ecological space optimization in the area. The findings provide a theoretical foundation for promoting high-quality development and optimizing ecological spatial governance policies in the Greater Huangshan Region.An index system for ecological space configuration optimization in the Greater Huangshan Region was constructed based on the DPSIR model, and the Entropy Weight-TOPSIS method was applied to evaluate the ecological space from 2018 to 2023. From a temporal dimension, the configuration optimization of ecological space in the Greater Huangshan Region showed an upward trend from 2018 to 2023, with a significant improvement in ES levels. From a spatial dimension, there are certain differences in the group optimization level of ecological space among cities in the region, with the spatial distribution generally showing the characteristics of Anqing > Huangshan > Xuancheng > Chizhou. Although the group optimization of ES in the Greater Huangshan Region has significantly strengthened from 2018 to 2023, the ecological situation remains severe. It is necessary to accelerate socioeconomic development while actively implementing various ecological protection policies, comprehensively improving the group optimization level of ecological space in each city, and thus promoting high-quality development in the Greater Huangshan Region.